Autocrine Human Growth Hormone Stimulates Oncogenicity of Endometrial Carcinoma Cells - Vijay Pandey; Jo K. Perry; Kumarasamypet M. Mohankumar; Xiangjun Kong; Shumin Liu; Zhengsheng Wu; Murray D. Mitchell; Tao Zhu; Peter E. Lobie (2008)
Recent published data have demonstrated elevated levels of human GH (hGH) in endometriosis and endometrial adenocarcinoma. Herein, we demonstrate that autocrine production of hGH can enhance the in vitro and in vivo oncogenic potential of endometrial carcinoma cells. Forced expression of hGH in endometrial carcinoma cell lines RL95-2 and AN3 resulted in an increased total cell number through enhanced cell cycle progression and decreased apoptotic cell death. In addition, autocrine hGH expression in endometrial carcinoma cells promoted anchorage-independent growth and increased cell migration/invasion in vitro. In a xenograft model of human endometrial carcinoma, autocrine hGH enhanced tumor size and progression. Changes in endometrial carcinoma cell gene expression stimulated by autocrine hGH was consistent with the altered in vitro and in vivo behavior. Functional antagonism of hGH in wild-type RL95-2 cells significantly reduced cell proliferation, cell survival, and anchorage-independent cell growth. These studies demonstrate a functional role for autocrine hGH in the development and progression of endometrial carcinoma and indicate potential therapeutic relevance of hGH antagonism in the treatment of endometrial carcinoma.